2003
DOI: 10.1128/aem.69.3.1488-1491.2003
|View full text |Cite
|
Sign up to set email alerts
|

Solar UV-B Radiation Inhibits the Growth of Antarctic Terrestrial Fungi

Abstract: We tested the effects of solar radiation, and UV-B in particular, on the growth of Antarctic terrestrial fungi. The growth responses to solar radiation of five fungi, Geomyces pannorum, Phoma herbarum, Pythium sp., Verticillium sp., and Mortierella parvispora, each isolated from Antarctic terrestrial habitats, were examined on an agar medium in the natural Antarctic environment. A 3-h exposure to solar radiation of >287 nm reduced the hyphal extension rates of all species relative to controls kept in the dark.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 16 publications
1
82
1
1
Order By: Relevance
“…Second, we hypothesized that UV would preferentially degrade the lignin fraction in litter, as its aromatic structure is known to absorb UV wavelengths (Austin and Ballare´2010) and is thought to undergo chemical changes when exposed to solar radiation (Lanzalunga and Bietti 2000). Finally, we hypothesized that the net result of UV is inhibition of microbial activity, given previous observations that UV can damage microbial DNA (Rohwer and Azam 2000), slow the growth of microbial communities (Hughes et al 2003), and result in altered microbial community composition (Caldwell et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we hypothesized that UV would preferentially degrade the lignin fraction in litter, as its aromatic structure is known to absorb UV wavelengths (Austin and Ballare´2010) and is thought to undergo chemical changes when exposed to solar radiation (Lanzalunga and Bietti 2000). Finally, we hypothesized that the net result of UV is inhibition of microbial activity, given previous observations that UV can damage microbial DNA (Rohwer and Azam 2000), slow the growth of microbial communities (Hughes et al 2003), and result in altered microbial community composition (Caldwell et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Foereid et al (2010) found evidence for facilitation in a lab study, but field studies have yet to determine how UV affects microbial properties in litter. UV could have detrimental effects on microbial communities, as it is known to damage microbial DNA (Rohwer and Azam 2000) and suppress growth of terrestrial microbes (Hughes et al 2003). On the other hand, UV facilitation of microbial communities could be especially important in semiarid Mediterranean ecosystems with marked seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…The indigenous fungi of Antarctica have been studied in soils (Kerry 1990a, b, Finotti 1993, Azmi et Seppelt 1998, Hughes et al 2003, Krishnan et al 2011, ice cores and permafrost (Gilichinsky et al 2005), lake sediment (Sugiyama et al 1967) and also in the air column (Marshall 1997). Airborne spores originating from South America have also been detected in the Antarctic Peninsula region (Marshall 1997).…”
Section: Antarctic Microfungal Diversitymentioning
confidence: 99%
“…In addition, only UV itself is known to have antifungal effects. 12,13 Based upon these considerations, we compared voriconazole single agent treatment with voriconazole plus UV-A combination therapy as a possible treatment for fungal keratitis.…”
mentioning
confidence: 99%